CeO2 Nanoparticles Reduce Oxidative Stress and Delay the Degeneration of Intervertebral Disc - Sheng-Jie Chang; Xin-Wei Zhang; Hao-Wei Xu; Shu-Bao Zhang; Xiao-Wei Liu; Yu-Yang Yi; Wei Pan; Kai Li; Shan-Jin Wang (Bioinorganic Chemistry and Applications)
The oxidative stress of the body can destroy the homeostasis and lead to a series of adverse outcomes. In recent years, nano-enzyme materials, as a new hotspot in materials science, have been gradually applied in various fields because of their enzyme-like activities at the nanoscale and their ability to regulate various physiological processes in organisms. In this study, we developed a novel cerium oxide (CeO2) nano-enzyme drug and demonstrated that the nano-enzyme can effectively improve oxidative stress levels and delay disc degeneration in rats. The experimental results confirmed that in in vitro experiments, the novel cerium oxide nano-enzyme could significantly reduce the ROS level in cells, delay cell senescence, reduce the level of apoptosis, and improve the metabolic state of nucleus pulposus cells. At the same time, it maintains low toxicity to cells. At the animal level, imaging and histomorphological evaluation showed that the novel cerium oxide nano-enzyme could significantly improve the disc height index, MRI Pfirrmann grade, and histological grade scores in rats. In summary, we have developed a successful cerium oxide nano-enzyme, which can be used to reduce the degeneration level of intervertebral disc and provide a new potential idea for clinical treatment of patients with lumbar disc herniation.